2017
DOI: 10.1097/md.0000000000008427
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative administration of morphine in alleviating intraoperative pain of percutaneous transforaminal endoscopic discectomy under local anesthesia

Abstract: Local anesthesia is routinely recommended for percutaneous transforaminal endoscopic discectomy (PTED). However, the intense intraoperative pain remains a serious problem. The purpose of the current study is to find a safe and effective method to alleviate the intense pain during PTED for lumbar disc herniation (LDH) under local anesthesia.This study retrospectively analyzed 63 LDH patients who accepted PTED under local anesthesia. Thirty-one patients received intramuscular injection of morphine before PTED, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…However, additional equipment, personnel, and medical costs limit the popularization of the technology. Although patients with local anesthesia retain consciousness, previous studies have shown that analgesia is insufficient [ 8 ], and various analgesic drugs are needed to remedy [ 9 , 10 ]. Epidural anesthesia can also retain the consciousness of patients and provide perfect analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional equipment, personnel, and medical costs limit the popularization of the technology. Although patients with local anesthesia retain consciousness, previous studies have shown that analgesia is insufficient [ 8 ], and various analgesic drugs are needed to remedy [ 9 , 10 ]. Epidural anesthesia can also retain the consciousness of patients and provide perfect analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the T group, the incidence of ∆SPI >15 was the lowest and occurred in only 13 cases (37.1%). This stands in opposition to various studies available in the literature, which showed an inability of topical anaesthesia to prevent discomfort or pain upon trocar insertion [ 26 ].…”
Section: Discussionmentioning
confidence: 59%
“…Another observation study by Fan et, al. demonstrated that intramuscular injection of morphine prior to PELD turns out to be overall effective, except for the increased risk of nausea and vomiting[26]. Our study is the first clinical trial to investigate the effect of ITM, a time-tested analgesia approach, as an adjuvant pain-relieving therapy on PELD.…”
Section: Discussionmentioning
confidence: 98%